Foliar epidermal anatomical characteristics of taxa of Iris subg. Scorpiris Spach (Iridaceae) from Turkey. Issue 6 (14th February 2019) - Kandemir, Nezahat; Çelik, Ali; Ullah, Fazal; Shah, Syed Nasar; Zaman, Wajid
Abstract: Iris L. is one of the important genus of family Iridaceae, consist of 56 taxa naturally occurred in Turkey. The similarities and variations in the subgenus overlapping the taxonomic positions of the species in the subgenera and needs anatomical assessment especially by microscopic techniques. In this study, the taxonomic significance of leaf anatomical characters of 10 Iris subgenus Scorpiris taxa were studied in detail and the relationship among these taxa were evaluated using microscopy techniques. Fresh leaf samples of species were fixed in 70% alcohol solution for anatomical observation under microscope. Eleven different micromorphological features were statistically analyzed to delimit the species in subgenus. Based on morphological and anatomical similarities, we studied relationships among; (1) ssp. turcica, ssp. caucasica, I. nezahatiae and I. pseudocaucasica ; (2) correlation between ssp. turcica and ssp. caucasica ; (3) association of I. galatica, I. persica, ssp. margaretiae and ssp. stenophylla with each other; (4) relationship between ssp. stenophylla and ssp. margaretiae ; and (5) relevance between I. aucheri and I. peshmeniana . Moreover, the taxonomy of subgenus Scorpiris has been discussed in detail with novel and diagnostic features based on micromorphological physiognomies. We found that four species in this study are endemic to Turkey, while seven are critically endangered geophytes in the country. The leaf anatomical characteristics of 10 taxa were divided into three groups. Main aim of this research was to study the taxonomy of the complex subgenus Scorpiris through microscopic techniques. Abstract : Foliar epidermal anatomy of Iris sub genus Scorpiris . Taxonomical characteristic of subgenus Scorpiris . Using microscopic techniques for the identification and species delimitation of species in Iris sub genus Scorpiris .